Developing Students’ Creative Thinking Skills Through Problem Solving Approaches to Geometry Materials in Grade 5 of Private Elementary School Banda Aceh - Fauzi Fauzi; Linda Vitoria; Said Darnius; Israwati Israwati (Proceedings of AICS - Social Sciences, 2021)
Creative thinking skills are needed by students to be able to deal with daily problems that arise unexpectedly. However, the fact is that mathematics learning still does not emphasize students’ creative thinking skills. This study aims to describe developing students' creative thinking skills through problem solving on Geometry material in grade 5 of Private Elementary School Banda Aceh. The method used is qualitative research with a descriptive research type with grounded theory research design. The subjects were 26 from grade 5 students of Private Elementary School Banda Aceh. The data of this study were sourced from the results of written tests and interviews. The data analyzed are creative thinking ability data (fluency, flexibility, and novelty aspects) and Creative Thinking Ability level data (TKBK). The results of the data analysis of creative thinking skills on the student’s fluency aspect obtained 69,3%, the student’s flexibility aspect was obtained 23% and the student’s novelty aspect was obtained 7.7%. The results of the data analysis of students’ TKBK leveling are at TKBK level 4 obtained 7,7%, TKBK level 3 obtained 11.5%, TKBK level 2 obtained 11.5%, TKBK level 1 obtained 54%, and level TKBK 0 obtained 15.3 %. The creative thinking ability of fifth graders at a private elementary school in Banda Aceh through a problem solving approach to geometry material can be concluded that it is “still very low”. This is evident from the data that students’ ability to solve problems in the novelty aspects is 7.7%.Keywords: Creative Thinking Skills, Problem Solving, Geometry Material.